Deconstructing screen time: The connections between digital use, dissatisfaction, and disconnection - Malene Hornstrup Jespersen; Kristoffer Albris; Helene Willadsen (Computers in Human Behavior Reports)
With the global permeation of digital technologies, concern has grown over the disadvantages of time spent on digital devices. Previous literature has studied these concerns either by focusing on one device or platform or by using catch-all phrases such as ‘screen time’. In this paper, our aim is to investigate the interrelations of different digital use cases and provide insights from which relevant conceptualizations of ‘screen time’ can be made. Adapting theories and measures of dissatisfaction with digital use and digital disconnection from previous studies, we divide screen time into thirty-four variables, and use this division to ask how different devices, platforms, and activities are related to people’s wishes to decrease their digital use and their propensity to disconnect. We draw our findings from a representative survey covering 9,524 individuals. Using OLS regressions, we find that dissatisfaction with passive and solitary entertainment predict both wanting to decrease digital use overall and the propensity to digitally disconnect. Further, we find that the wish to decrease smartphone use is the most impactful predictor of wanting to decrease digital use overall. It is, however, not a significant predictor of the propensity to disconnect. This gap between intentions and actions suggests that the physical presence of the smartphone negatively impacts individuals’ experienced balance in their digital use. Our study contributes by highlighting that research focusing on only one component of screen time (such as Facebook), as has been common, risks overstating the impact on digital (dis)satisfaction and disconnection behavior of that component because important interrelated factors are left out.